Operatividad del departamento de consejería estudiantil de las escuelas municipales del cantón Loja frente a casos de violencia sexual infantil - Abad Pérez, Karla Anahí (2022)
The present academic research work entitled "Functioning of the Department of Student Council of the municipal schools of the Loja Canton in Child Sexual Violence cases”, arises from the interest in investigating the rights violation and the principle of higher interest in the educational field before the action or professionals inaction who integrate the Department of Student Orientation (DECE) in relation to protocols and routes of action in violence detected cases or committed in the educational institution, to show the children helplessness and adolescents when their injuries are found rights, especially their sexual integrity. Therefore, with the study and the fundamental concepts research, it has been possible to collect relevant information that deals with the joint actions to be accomplished. In this thesis, materials and methods were applied that allowed the development of the research, in the same way interviews were conducted with psychoeducational professionals, psychologists and social workers, the results of ignorance on the part of execution of the obtained protocols served to arrive at important conclusions and recommendations, which will ensure compliance with regulations and the integrity of children and adolescents